If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8+6a=-6+8a
We move all terms to the left:
8+6a-(-6+8a)=0
We add all the numbers together, and all the variables
6a-(8a-6)+8=0
We get rid of parentheses
6a-8a+6+8=0
We add all the numbers together, and all the variables
-2a+14=0
We move all terms containing a to the left, all other terms to the right
-2a=-14
a=-14/-2
a=+7
| 3(r+4)-2r=-5 | | f(3)=2(3)(6)-4(3) | | 18x-9=4x+5 | | v+4/5=9/5 | | 4x-2x+7=-21 | | 4-10x=44 | | 11x+15=6x+70 | | 447+x=−261 | | 15+4h=3+6h | | -3-4n=1-6n | | 9+2m-5-3=5m-5 | | 192=44-x | | y/3=1/21 | | 46=5x+3(x+2) | | a÷-2+9=30 | | b/2-5=6 | | 5+5u=6u-4 | | 16j+18=-20-10+20j | | 2u-1=-9-2u | | 13b+19=12b | | 2x+18x-10=47 | | 6-2j=10 | | x+3,000=21,000 | | 2x+4=-4x+5 | | 1=13+r/9 | | 35x+55-10x+28x+75-5x+12=0 | | 16=-8(7+p) | | 12x-4=8x24 | | x=25+10-20 | | 25h=15h+75 | | 7u-47=3(u-9) | | 23x+34=23-12x7x |